Implementation of Active Learning Strategies in Islamic Religious Education in Primary Schools - Devi, Nofrizal; Satrial, Ardi; Indria, Anita; Asril, Zainal (Khalaqa: Journal of Education and Learning, 2024)
This research is based on the lack of awareness of students in PAI learning. Students are less active and less enthusiastic in participating in learning because the learning strategies carried out by PAI teachers are still monotonous. Several types of active learning strategies have been carried out by PAI teachers, but they still do not involve active students, so students are less enthusiastic and learning is less interesting for students. This research aims to find out the types of active learning learning strategies, the steps for implementing active learning learning strategies, and to find out the advantages and disadvantages of active learning learning strategies in PAI subjects in elementary schools. This type of research is qualitative descriptive research. The data sources are school principals, PAI teachers, and students. Data collection was obtained using interviews, observation, and documentation. Data analysis techniques: data reduction, data presentation, and conclusions or verification. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.